(untitled) (Baghdad Science Journal, 2012)
This study aimed to know the concentration of elements content in dairy products. Nine samples collected from the local market in Baghdad, two samples of milk and seven of yoghurt.The results were followed: The ratio of Aluminum In Aluminum cans That is used for storage milk and industrialize yoghurt is about 95.5% ,this ratio is against [1] which said that pureness of Aluminum used in Aluminum cans should not be less than 98-99% . and the ratio of Cadmium reached to 0.001% which is also against [1] which assure that the Aluminum cans should be clean from that element, mean while the concentration of Iron, Copper and Zinc were within the standard level. The highest concentration of Iron was in treatment B2(canon yoghurt)it was 9.95 mg/L while the lowest concentration 4.1 mg/L was in treatment B1 (lab yoghurt). The highest concentration of Copper appeared in treatment B5 it was 4.63 mg/L while the lowest concentration 0.21 mg/L was in treatment B7. The results of this study illustrate that the increase of Zinc in all treatments. The highest level reached to 17.27 mg/L in B3 treatment (Al-washash yoghurt) and 5.18 mg/L as a lowest concentration in B1 treatment (lab yoghurt). The analytic results showed that all of the treatments were cleaned from lead. The highest concentration of Cadmium reached to 0.070 mg/L in B5 treatment (dragh yoghurt) and the lowest concentration reached to 0.023 mg/L was in B4 (Arbeel yoghurt) while treatment B1(lab yoghurt) and B7(kadmiaa yoghurt) were clean from Cadmium concentration when receipt.